Μελέτη λυγισμού σε πλοίο Bulk Carrier, βάσει των Common Structural Rules, με τη μέθοδο των πεπερασμένων στοιχείων - Μπαλωτή, Κωνσταντίνα (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ναυπηγών Μηχανολόγων Μηχανικών. Τομέας Θαλάσσιων Κατασκευών, 2018)
This diploma thesis studies the buckling capacity of structural components of Bulk Carriers based on the methodology introduced in the Common Structural Rules for Oil Tankers and Bulk Carriers 2017. The study is carried out in the middle cargo hold of a modern Bulk Carrier with a total deadweight tonnage of 61,462t. An extensive description and commentary of the procedures prescribed by the Regulations is given and is followed by the application of the buckling strength check using the finite elements method. The modelling was carried out as a three-hold compartment and for one sagging dynamic load case and an alternate loading condition, using ABAQUS/CAE software. The response of the structure was the result of the sea pressure on the outer shell of the hull and the weight of structural steel and cargo. In addition, bending moments were applied on both ends of the model, in order to achieve the target shear force at the aft bulkhead of the middle hold and the target maximum bending moment. The analysis of the results was based on Regulation procedures by dividing the construction is simple plate panels and checking the panel buckling capacity using the plate limit state interaction formulae. The analysis revealed that the components under consideration display sufficient buckling capacity.